Press Metal Aluminium Holding Berhad Vertical investment project – carbon anodes - Choa, Wei Keong (2024)
Press Metal Aluminium Holdings Limited is Southeast Asia's largest integrated aluminium producer with an annual capacity of 1.08 million tons for aluminium smelting and 210,000 tons for extrusion activities. Harnessing Sarawak's hydropower supply has made the company a low-cost, low-carbon emission metal and remains competitive in the market.